Solutions for a Class of Hadamard Fractional Boundary Value Problems with Sign-Changing Nonlinearity. (4th February 2019) - Zhang, Keyu; Fu, Zhengqing
Abstract : Using fixed point methods we establish some existence theorems of positive (nontrivial) solutions for a class of Hadamard fractional boundary value problems with sign-changing nonlinearity.